Sustainability and Public Policy for the Sugar-Energy Industry: An Analysis of the Topics Covered - Duarte, Carla Grigoletto (2015)
The sugar cane industry is historically important for the Brazilian economy and, more recently, it has also become important in discussions about sustainability due to its potential to offer renewable energy and thus contribute to reducing greenhouse gases emissions. To deal with the development of this sector, state and federal governments have been formulating policies related to various sustainability issues. In this context, the purpose of this paper is to identify the scope of sustainability issues approached by the current framework of policies for the sugar cane sector, in order to discuss what themes are regarded as priorities enough to be implemented as a policy. The methods include qualitative analysis using open grid analysis for coding, and the discussion of the results is based on the five dimensions of sustainability as proposed by Sachs (2007). Eighteen initiatives related to sixteen environmental, social, economic/financial, scientific/technological and medium- and long-term planning were identified. The set of established policies indicates that government action has been broad, resulting in initiatives related to several sustainability issues, like water, biodiversity, occupational health and employment and income. The fact of policies having been drawn up and published, regardless of the motives, can be seen as an appreciation of these issues by policy makers.